Finishing Beef - Dhuyvetter, Kevin C.; Tonsor, Glynn T. (My University, 2014)
This publication helps a producer that buys feeder calves and then finishes them, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF592_2014_04
Keywords: MF592; Economics; Livestock; MF